DETERMINANTS OF FACTORS AFFECTING THE USE OF E-PAYMENT (QRIS) IN MSMES IN MALANG CITY - Ulhaq, Rifqi Dhiya; Permatasari, Ditya (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research aims to determine and analyze the influence of perceived usefulness, perceived ease of use, perceived risk, and trust on behavioral intention to use, and behavioral intention to use on actual system use in MSMEs in Malang City. The population in this research is MSMEs that use e-payment in the form of QRIS in Malang City. This research uses quantitative methods with a descriptive approach. In this research, researchers used Partial Least Square (PLS) or SmartPLS software, which is run using computer media. The sample from this research was 110 respondents. Data collection was carried out by distributing questionnaires in the form of a Google form. The results of this research show that the variables perceived usefulness, perceived ease of use, and perceived risk do not have a positive influence on behavioral intention to use, while the variable trust has a significant influence on behavioral intention to use, and the variable behavioral intention to use has a significant influence. significant to actual system use